Trade Liberalization Under the GATT, the NAFTA and the EU:: Selected Topics - Baggaley, Nicholas (Journal of Comparative International Management, 1998)
Multilateral free trade has taken on increasing global importance with the passage of such agreements as the NAFTA, the EU, the GATT, and the recent transformation of the latter into the WTO. The underlying principle of each is progressive trade liberalization in all fields of economic activity, including those which are more prone to protectionist forces such as agriculture, financial services, and foreign direct investment. In aiming to promote progressive trade liberalization, the GATT, the NAFTA and the EU contain rules designed to guard against wrongful trade practices, for example an exporter "dumping" cheap products in a foreign market. This paper critically examines the degree to which these agreements reach their objective, and concludes that although they facilitate the removal of trade restrictions and other barriers, they do not go far enough in a number of specific areas. Examples are provided.